Advances in Affective and Pleasurable Design Proceedings of the AHFE 2018 International Conference on Affective and Pleasurable Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Fukuda, Shuichi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the latest advances in affective and pleasurable design. Further, it reports on important theoretical and practical issues, covering a wealth of topics including aesthetics in product and system design, design-driven innovation, affective computing, evaluation tools for emotion, Kansei engineering for products and services, and many more. Based on the AHFE 2018 International Conference on Affective and Pleasurable Design, held on July 21-25, 2018, in Orlando, Florida, USA, the book provides a timely survey and inspiring guide for all researchers and professionals involved in design, e.g. industrial designers, emotion designers, ethnographers, human-computer interaction researchers, human factors engineers, interaction designers, mobile product designers, and vehicle system designers. .
Increasing importance of emotion in the connected society -- Shanghai Shikumen cultural and creative product design based on design thinking -- Modeling subjective temperature using physiological index -- On poster design in the subway public space in China based on the regional culture -- Verification of brain activity when watching TV commercials using optical topography -- Improved user experience with emotional design -- Applying intuitive thinking in smart home design based on semantic association -- The impact of design semantic on the user emotional image in the interface design -- Music retrieval and recommendation based on musical tempo.
Keywords: Computational intelligence; Engineering design; Emotions; Industrial engineering; Production engineering; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Engineering Design; Emotion; Industrial and Production Engineering; User Interfaces and Human Computer Interaction